Migration dynamics - Oded Stark; You Qiang Wang (Institute for Advanced Studies (IHS), 2002)
Quite often established migrants offer assistance and support that facilitate the arrival of new migrants. Why would migrants want other migrants to join them - so much so as to be willing to pay for them to come? We suggest a rationale. Our modeling framework is capable of explaining several stylized facts pertaining to transfers by migrants and the structure and dynamics of migration.
Keywords: F22; J61; 330; migration dynamics; migrants' transfers; follow-up migration; Rücküberweisung (Migranten); Theorie; Migrationstheorie